Animal Answers to the Jewish Question: Review of Jay Geller, Bestiarium Judaicum: Unnatural Histories of the Jews - Jacobs, Joela (Humanimalia, 2019)
Jay Geller. Bestiarium Judaicum: Unnatural Histories of the Jews. New York: Fordham University Press, 2018. 404 pp. $75 hb.